Evaluation of the efficacy of a novel Vibrio vulnificus vaccine based on antibacterial peptide inactivation in turbot, Scophthalmus maximus. Issue 118 (November 2021) - Gu, Qin-qin; Wang, Guang-hua; Li, Ning-qiu; Hao, Dong-fang; Liu, Hong-mei; Wang, Chang-biao; Hu, Yong-hua; Zhang, Min
Abstract: Tongue sole tissue factor pathway inhibitor 2 (TFPI-2) C-terminus derived peptide, TC38, has previously been shown to kill Vibrio vulnificus cells without lysing the cell membrane; thus, the remaining bacterial shell has potential application as an inactivated vaccine. Therefore, this study aimed to evaluate the immune response induced by the novel V. vulnificus vaccine. The protective potential of TC38-killed V. vulnificus cells (TKC) was examined in a turbot model. Fish were intramuscularly vaccinated with TKC or FKC (formalin-killed V. vulnificus cells) and challenged with a lethal-dose of V. vulnificus . The results showed that compared with FKC, TKC was effective in protecting fish against V. vulnificus infection, with relative percent of survival (RPS) rates of 53.29% and 63.64%, respectively. The immunological analysis revealed that compared with the FKC and control groups, the TKC group exhibited: 1) significantly higher respiratory burst ability and bactericidal activity of macrophages at 7 d post-vaccination; 2) increased alkaline phosphatase, acid phosphatase, lysozyme, and total superoxide dismutase levels post-vaccination; 3) higher serum agglutinating antibody titer with corresponding higher serum bactericidal ability, and a more potent serum agglutination effect, as well as an increased IgM expression level; 4) higher expression of immune relevant genes, which were involved in both innate and adaptive immunity. Taken together, this is the first study to develop a novel V. vulnificus inactivated vaccine based on AMP inactivation, and TKC is an effective vaccine against V. vulnificus infection for aquaculture. Highlights: TKC was generated by using TC38, a tongue sole TFPI-2 C-terminus derived peptide. Fish vaccinated with TKC exhibited greater protection than that of FKC. TKC stimulated higher innate and adaptive immune response in turbot than FKC.